Epilogue - Csapó, Benő; Funke, Joachim (The nature of problem solving, 2017)
As we finish the work of editing this book and look back at the process behind that effort, we have the feeling that it has simultaneously been one of the most inspiring experiences and one of the most challenging undertakings of our professional careers. The idea of creating a book on the state of the art of problem solving research was conceived in a series of formal and informal meetings among the authors, and it has been shaped in a number of discussions and e-mail exchanges since then.
Gesehen am 12.06.2017